HEALTHCARE TECHNOLOGIES USED IN NURSING TO CARE FOR POLYTRAUMATIZED PATIENTS: AN INTEGRATIVE REVIEW - Virna Ribeiro Feitosa Cestari; Luís Rafael Leite Sampaio; Islene Victor Barbosa; Rita Mônica Borges Studart; Bruna Bárbara Fernandes Moura; Ana Rachel Cavalcante Araújo (Universidade Federal do Paraná, 2015)
The aim of this study was to identify healthcare technologies used by nurses in the care for polytraumatized patients. This is an integrative review, with articles found in three databases in the period from May to July 2014. Nineteen articles from the period between 2009 and 2014 were selected and distributed among the three categories of healthcare technology: soft, soft-hard and hard. It was found that nursing workers adopted the three types of healthcare technology when caring for polytraumatized patients, emphasizing the soft-hard category. Soft technologies included health support and education of patient and family members/caregivers and training of the nursing team; soft-hard technologies: care management, admission of patients under risk, assessment and treatment of pain, nursing process and development of protocols; and hard technologies: information systems. Care improvements caused by healthcare technologies were found, since they reach all aspects of care.